Doping of two-dimensional MoS2 by high energy ion implantation. (26th October 2017) - Xu, Kang; Zhao, Yuda; Lin, Ziyuan; Long, Yan; Wang, Yi; Chan, Mansun; Chai, Yang
Abstract: Two-dimensional (2D) materials have been demonstrated to be promising candidates for next generation electronic circuits. Analogues to conventional Si-based semiconductors, p - and n -doping of 2D materials are essential for building complementary circuits. Controllable and effective doping strategies require large tunability of the doping level and negligible structural damage to ultrathin 2D materials. In this work, we demonstrate a doping method utilizing a conventional high-energy ion-implantation machine. Before the implantation, a Polymethylmethacrylate (PMMA) protective layer is used to decelerate the dopant ions and minimize the structural damage to MoS2, thus aggregating the dopants inside MoS2 flakes. By optimizing the implantation energy and fluence, phosphorus dopants are incorporated into MoS2 flakes. Our Raman and high-resolution transmission electron microscopy (HRTEM) results show that only negligibly structural damage is introduced to the MoS2 lattice during the implantation. P-doping effect by the incorporation of p + is demonstrated by Photoluminescence (PL) and electrical characterizations. Thin PMMA protection layer leads to large kinetic damage but also a more significant doping effect. Also, MoS2 with large thickness shows less kinetic damage. This doping method makes use of existing infrastructures in the semiconductor industry and can be extended to other 2D materials and dopant species as well.